My Bengkel Application to Facilitate Bookkeeping for Small and Medium Enterprises in the Automotive Sector - Qoriani Widayati; Irman Effendy; Siti Nurhayati; Msy. Mawaddah Utama Putri (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
Small and Medium Enterprises (SMEs) are an important part of the economy of a country or region, as well as in Indonesia, these SMEs play a very important role in the speed of the people's economy. These SMEs are also very helpful to the state/government in terms of creating new jobs and through SMEs many new work units are created that use new workers who can support household income. Simple bookkeeping is a standard that must be owned by all SME business people. It is often found that small business actors or SME businesses have never recorded all of their business activities. They don't even use a simple bookkeeping example to help manage and regulate all financial traffic. From these problems, this research seeks to find the right solution where researchers plan to make a business bookkeeping application to make it easier for SMEs. One type of UKM that is the object of this research is the Automotive Workshop field. The workshop is one type of business that is needed by the community, because of that computerized bookkeeping is needed. By using the prototype software development method. The results of this research are in the form of the My Bengkel application which will later be equipped with several features ranging from Sales, Purchases, Expenses, Receipts, Inventory to Payables and Accounts Receivable